Adrenergic response patterns in vas deferens isolated from rats under diurnal rhythms - Influence of stress - Leite-Kassuya, C. A.; Pereira, OCM (Elsevier B.V., 2005)
The aim of this study was to verify, by means of functional methods, whether the circadian rhythm changes adrenergic response patterns in the epididymal half of the vas deferens isolated from control rats as well as from rats submitted to acute stress. The experiments were performed at 9:00 a.m., 3:00 p.m., 9:00 p.m., and 3:00 a.m. The results showed a light-dark dependent variation of the adrenergic response pattern on organs isolated from control as well as from stressed rats. In the control group, only the phenylephrine sensitivity was changed throughout the circadian rhythm. Under the stress condition, both norepinephrine and phenylephrine response patterns were changed, mainly during darkness. The maximal contractile response to both alpha- and beta-agonist and alpha(1)-agonist was increased in the dark phase, corresponding to high plasmatic concentrations of endogenous melatonin. The vas deferens isolated from stressed rats during the light phase simultaneously incubated with exogenous melatonin showed the same pattern of response obtained in the dark phase, thus indicating a peripheric action of melatonin on this organ. Therefore, the circadian rhythms are important to the adrenergic response pattern in rat vas deferens from both control and stressed rats. In conclusion, we suggest a melatonin modulation on alpha(1)-postsynaptic adrenergic response in the rat vas deferens. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: norepinephrinel; melatonin; light-dark cycle; circadian rhythms; stress; vas deferens; rat